Formation of aggregate demand for labor force in the context of national economy structural transformation - Ilich, L. M. (Statistics of Ukraine, 2016)
The article is focused on the problem of demand formation for labor force in the movement of national economy structural transformation. The dynamics of Ukrainian economy structural transformation within the period of 1990-2014 is investigated. Rate factors and structural changes efficiency showing regarding the demand for labor force within the period of 2004-2014 are estimated. They concern economic activity, occupation groups, jobsite types and regions. The main tendencies in formation of aggregate demand for labor force and risks for national labor market are defined. National economy structural transformation research and their effect on formation of aggregate demand for labor founds to claim that jobsites gradual redistribution for benefit of service economy is characteristic to national labor market. That, on the one hand, requires special vocational training and is linked to performance of intellectual-capacious operations, but on the other hand, needs maintenance skills. Considering such tendencies, occupational and qualification structure of labor demand will transform towards involvement of qualified labor force, possessing high level of intellectual potential and skills of several occupations, in production. In such a way the profile of synthetic trade representatives will widen. The combination of the main occupation and informational labor will be of peculiar feature in Ukrainian employment prospective model, which requires qualitative new vocational training. In the current situation ensuring of efficient demand for labor force formation does not only depend on the macroeconomic indicators enhancement, but also on creation of effective institutional cooperation among all the stockholders. Nowadays recovery of business confidence in the government is one of the state primary goals. In this movement realization of anticorruption reforms is of great urgency. It will favor guaranteeing of all market participants’ equal access to the information of public importance, transparency of public purchases process, elimination of economical pressure on business. Furthermore, improvement of tax reformation is to become one of the business incentives instruments. It will provide the identical conditions for all the subjects of entrepreneurial activity diminish the pressure on small- and medium-sized business and promote the solution to the problem concerning recovery of value-added tax. Efficient demand for labor force formation in Ukraine requires development of labor market monitoring informational support. In particular, it is necessary to update labor tracking at the enterprises. Nowadays getting the information on new, liquidated, permanent, seasonal and temporary workplaces, their distribution as for economic activity, regions, jobsites categories, main occupational groups is hardly possible. Thus, prospective research into formation of efficient demand for labor force should be targeted at searching for the ways of labor market monitoring improvement.